2005
DOI: 10.1146/annurev.cellbio.21.122303.133159
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Lymphocyte Trafficking

Abstract: Over the past decades, intravital microscopy (IVM), the imaging of cells in living organisms, has become a valuable tool for studying the molecular determinants of lymphocyte trafficking. Recent advances in microscopy now make it possible to image cell migration and cell-cell interactions in vivo deep within intact tissues. Here, we summarize the principal techniques that are currently used in IVM, discuss options and tools for fluorescence-based visualization of lymphocytes in microvessels and tissues, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
137
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(139 citation statements)
references
References 95 publications
1
137
0
1
Order By: Relevance
“…Moreover, Chen et al (5) showed that LN NK cells efficiently lysed tumor cells and suppressed B16 melanoma metastasis to draining LN. These findings suggest that NK cells actively patrol the LN in search of cognate target and transformed cells, perhaps exhibiting robust motility similar to other lymphocyte subsets, such as T and B cells (6,7). Therefore, it was surprising that NK cells isolated by DX5-positive selection were reported to move with slow velocity (2.75 Ϯ 0.17 m/min) when imaged in LN by two-photon microscopy (8).…”
mentioning
confidence: 99%
“…Moreover, Chen et al (5) showed that LN NK cells efficiently lysed tumor cells and suppressed B16 melanoma metastasis to draining LN. These findings suggest that NK cells actively patrol the LN in search of cognate target and transformed cells, perhaps exhibiting robust motility similar to other lymphocyte subsets, such as T and B cells (6,7). Therefore, it was surprising that NK cells isolated by DX5-positive selection were reported to move with slow velocity (2.75 Ϯ 0.17 m/min) when imaged in LN by two-photon microscopy (8).…”
mentioning
confidence: 99%
“…Apart from using different guidance receptors, such as GPCRs and RTKs, cells also differ in whether, under physiological conditions, they migrate individually (5) or collectively, as part of a group (6). When migrating individually, each cell is expected to detect and respond to spatial cues directly and independently.…”
mentioning
confidence: 99%
“…In contrast to CFDA-SE, rhodamine 6G, a fluorescent membrane-permeable dye accumulating in mitochondria, has been used in countless IVM experiments. Upon intravenous injection, the dye selectively labels leukocytes and platelets in vivo, and its unbound portion is rapidly cleared from the circulation [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…Acridine orange presents with limitations due to its accumulation in parenchymal tissue and its potential light-induced phototoxic effect that alters hemodynamics and cell adhesion. The same holds true for rhodamine 6G, the widely applied dye for in vivo labelling of leukocytes for IVM studies [7,8]. In contrast, carboxyfluorescein diacetate succinimidyl ester (CFDA-SE) has been rarely applied for IVM investigations [9][10][11] even though it is discussed as an ideal dye for flow cytometry-based proliferation studies [5,6,12].…”
Section: Biophotonicsmentioning
confidence: 99%